Patent Troglostrongylus brevior-, Aelurostrongylus abstrusus-, Angiostrongylus sp.-, and Crenosoma sp. infections in wild Eurasian lynxes (Lynx lynx) and their habitat-sharing gastropod intermediate hosts - Haas, Marcel; Segeritz, Lisa; Anders, Ole; Middelhoff, Tomma Lilli; Myat Tun, Akary; Hasheminasab, Seyed Sajjad; Cocchiararo, Berardino; Dusch, Alena; Taubert, Anja; Hermosilla, Carlos (Frontiers in Veterinary Science, 2025)
The formerly widely spread Eurasian lynx (Lynx lynx) nowadays represents an endangered large wild felid species in Germany. Recent and ongoing conservation efforts have succeeded in establishing small but stable lynx populations in distinct parts of Germany. However, very little is known on the occurrence of neglected and re-emerging gastropod-borne cardiopulmonary nematodes in wild L. lynx populations in Europe. Therefore, the aim of current study was to estimate metastrongyloid infections in, a group of seven free-ranging, (sub-) adult Eurasian lynxes from the Harz Mountains (Germany) which were equipped with GPS/GSMS collars and in resident gastropod intermediate host populations. Both, lynx scat samples (n = 24) and terrestrial gastropods (n = 153) were collected in close proximity to prey remains left behind by Eurasian lynxes respectively in natural habitats in a non-invasive and un-molested manner. Fresh fecal samples were analyzed for the presence of metastrongyloid first-stage larvae (L1) by standard Baermann funnel technique and morphologically identified to genus level. Morphological metastrongyloid L1 were additionally investigated by PCR for final species identification. Terrestrial gastropods (i.e., slugs, semi-slugs, snails) were morphologically identified to genus level, thereafter artificially digested and analyzed for the presence of lungworm larvae. This work delivers a first report on the occurrence of patent Troglostrongylus brevior-, and Crenosoma sp.-infections in wild Eurasian lynxes in Germany and re-confirms recent findings on Aelurostrongylus abstrusus- and Angiostrongylus sp. infections in these lynxes. Overall, a total lungworm occurrence of 37,5% (9/24) was detected in assessed Eurasian lynx samples and 51.1% (4/7) of lynxes showed patent metastrongyloid infections. In digested terrestrial gastropods, 1.3% (2/153) contained A. vasorum larvae, underlining a successful propagation of A. vasorum life cycle in the Harz Mountains. Hence, we recommend regular monitoring for metastrongyloid infections not only in wild Eurasian lynxes but also in obligate intermediate hosts to better understand their impact on animal and population health to support current conservation efforts on this endangered large felid species in Europe.